Comeniology as a process and result of scientific cognition. Social context of education in the thought of John Amos Comenius - Dobrowolska, Barbara (Siedleckie Zeszyty Komeniologiczne seria Pedagogika, 2019)
The research paper is an attempt to justify the importance of comeniology in the humanities and social sciences. Furthermore, it includes some interpretation of the social con-texts of education appearing in the writings by Comenius. The justification of the meaning and nature of comeniology is based on the science term senses by T. Pilch and T. Bauman. Their academic coursebook, Zasady badań pedagogicznych (Principles of Pedagogical Research), is a classic methodological title in pedagogical literature. They give didactic, institutional, content, historic-sociological and functional substance to the idea of science. Each of these substances has been analyzed with respect to comeniology. The scientific category of comeniology covers the whole system of contents involving various stages of human developments and his existence. Social and political conditions become the objects of analyses and interpretation, which conse-quently generate more and more new ideas, statements, interpretations and reinterpretations referring to the works and thoughts of Comenius. Considering the methodology of research of the said works, comeniology is dominated by phenomenology and hermeneutics and their phil-osophical approach. Scientific discovery, research and methodological solutions along with the emerging system of knowledge about Comenius allow one to award comeniology the character of humanistic reflection. Due to the multi-disciplinary nature of the subject matters investigated, this reflection concerns the humanities and social sciences. Giving comeniology the status of scientific quality is considering its development in the categories of the process and result of scientific cognition. Reflections on comeniology’s scientific quality and discourse correspond to social issues. Due to the author’s personal interest in social pedagogy, an attempt has been made to indicate social contexts of education. They constitute a largely unexplored area of the works of Comenius and require further analyses. They encompass, inter alia, the issues of school as a social institution, equal access to education, poverty, social inequality and exclusion.